Niemann Pick Disease: A Case Report - Khan, Shareen; Jolly, Ferdous Akhtar; Baki, Md Abdul; Nahar, Jebun; Mohsin, Fauzia; Begum, Tahmina; Nahar, Nazmun (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Niemann Pick disease is a rare lysosomal storage disease of infancy which occurs due to accumulation of sphingomyelin in various tissues of the body. This leads to characteristic features of failure to thrive, marked organomegaly and neurodegenerative regression. The disease is uncommon in South East Asia and here we present this case as it is rarely found in Bangladesh. J Bangladesh Coll Phys Surg 2022; 40: 209-212